Cosmetic Surgery In Islamic Jurisprudence: A Comparative Analytical Study With Contemporary Medical Law - Ali G Al Zuraib, Mohammd (Journal of Neonatal Surgery, 2025)
Cosmetic surgery has seen tremendous growth in recent decades, driven by medical advancement and societal trends toward aesthetic enhancement. While these procedures are widely accepted in modern medical practice, they remain the subject of legal, ethical, and religious debate, especially in Islamic jurisprudence. This study aims to analyze cosmetic surgery through a juristic lens, examining classical and contemporary Islamic positions regarding bodily modification, and comparing these with current medical laws and ethical frameworks. The study explores jurisprudential principles concerning necessity (ḍarūrah), removal of harm (rafʿ al-ḍarar), and the sanctity of the human body (ḥurmat al-jasad). It further evaluates legal standards such as informed consent, professional responsibility, and the distinction between therapeutic and elective interventions. Ultimately, Islamic jurisprudence offers a balanced, maqāṣid-based framework that integrates medical ethics with moral and legal accountability..